Transient constrictive pericarditis: A complication of COVID-19 infection or first presentation of systemic lupus erythematous? A case report - Saghar Mehrban, MD; Razieh Omidvar, MD; Somayeh Sadat Jalali, MD; Hamidreza Pouraliakbar, MD; Maryam Favaedi, MD; Simin Almasi, MD (Radiology Case Reports, 2023)
Cardiovascular disorders are significantly associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Herein, we describe a case of myopericarditis and subsequent transient constrictive pericarditis after coronavirus disease 2019 (COVID-19). Three weeks following a mild SARS-CoV-2 illness, a 53-year-old woman was referred to the hospital with acute pleuritic chest pain, which was not attributable to any known cause and was only temporarily relieved. The pain persisted for the next few weeks until her second COVID-19 infection, which occurred 5 months after her first affliction. This time, Transthoracic echocardiography (TTE) revealed mild pericardial effusion, and cardiac magnetic resonance imaging (CMR) confirmed myopericarditis, leading to the administration of anti-inflammatory therapy for the patient. Despite a relative resolution of symptoms, her second CMR performed 8 months later revealed active perimyocarditis with transient constrictive pericarditis (CP).Additionally, fluorescent antinuclear antibody (FANA) and antimitochondrial Ab M2 (AMA) were tested positive for the first time. Thereafter, the patient was started on concurrent anti-inflammatory and immunosuppressant therapies, which were effective after 3 months. The transient CP was resolved, and there was no sign of active pericarditis on her last echocardiography. Acute pericarditis and its subsequent constrictive pericarditis are infrequent adverse outcomes of COVID-19. The unique feature of this case is the uncertainty regarding the underlying reason for cardiac complications, whether it is the first presentation of systemic lupus erythematosus (SLE) or viral-induced myopericarditis followed by a consequent transient CP.